Biological control of Fusarium crown rot of wheat with Chaetomium globosum 12XP1-2-3 and its effects on rhizosphere microorganisms - Feng, Chaohong; Xu, Fei; Li, Lijuan; Zhang, Jiaojiao; Wang, Junmei; Li, Yahong; Liu, Lulu; Han, Zihang; Shi, Ruijie; Wan, Xinru; Song, Yuli (Frontiers in Microbiology, 2023)
Chaetomium (C.) globosum is a common plant endophytic fungi that exhibits great biocontrol potential in plant disease. Fusarium (F.) crown rot (FCR) is an important disease in wheat that seriously threatens wheat production worldwide. The control effect of C. globosum against wheat FCR remains unclear. In this study, we introduced an identified C. globosum 12XP1-2-3 and tested its biological control potential against wheat FCR. The hypha and fermentation broth exhibited an antagonistic effect against F. pseudograminearum. Results from indoor experiments showed that C. globosum 12XP1-2-3 might delay the onset of symptoms of brown stem base and significantly reduce the disease index (37.3%). Field trials showed that wheat seeds coated with a spore suspension of 12XP1-2-3 grew better than the control seeds, had control effects of 25.9% to 73.1% on FCR disease, and increased wheat yield by 3.2%–11.9%. Analysis of rhizosphere microorganisms revealed that seeds coated with C. globosum (‘Cg’ treatment) had a greater effect on fungal rather than on bacterial alpha diversity and may improve the health state of rhizosphere microorganisms, as reflected by the significantly increased fungal Shannon index at Feekes 11 and the increased complexity of the bacterial co-occurrence network but decreased complexity of the fungal network. Moreover, the accumulation of beneficial bacteria such as Bacillus and Rhizobium at Feekes 3, and Sphingomonas at Feekes 7 in the ‘Cg’ treatment may be the important contributions to healthier wheat growth state, significantly reduced relative abundance of Fusarium at Feekes 11, and reduced occurrence of FCR disease. These results provide a basis for further research on the mechanism of action of C. globosum and its application in the biological control of FCR in the field.